Pré-condicionamento com L-alanil-glutamina na lesão aguda de isquemia e reperfusão cerebral em gerbils - Pires, Vilma Leite Sousa (2010)
We investigated the metabolic effects of L-alanyl-Glutamine (L-ALN-GLN) on blood and tissue concentrations of metabolites (lactate, pyruvate, glucose and ketone bodies), thiobarbituric acid reactive substances (TBARS), glutathione (GSH), myeloperoxidase (MPO) and histopathologic evaluation of gerbils. This was an experimental and controlled study. Fifty-four male gerbils with a mean weight of 150gwere used, and were divided randomly and equally into 3 groups: saline with ischemia and reperfusion (SIR), saline without ischemia and reperfusion (SSI), L-alanyl-glutamine ischemia and reperfusion (GIR). They were then redistributed into three subgroups: T0 (maximum time of ischemia), T30 (30 min of reperfusion) and T60 (60 min of reperfusion), containing 6 animals each. They were pretreated with saline 2.0 mL 0.9% intra-venous (iv) or ALN-L-GLN 0.75 g / kg (iv) 30 min before the start of the experiments. Cerebral ischemia was induced by bilateral occlusion of the common carotid arteries (CCAs) for a period of 15 minutes. After all surgical procedures, the samples (blood and tissue) were collected at the end of the three periods. When comparing SSI and SIR groups, a significant increase of lactate was found in SIR group in T0 (0.756±0.091 versus 3.596±1.546; p=0.0122, T30 (0.869±0.254 versus 3.316±1.356); p=0.0015, and T60 (0.858±0.460 versus 2.409±0.801); (p=0.0122). In brain tissue there was significant lactate increase in TO (1.374±0.172 versus 2.530±0.850); p=0.0085, T30 (0.891±0.697 versus 1.840±0.530); p=0.0243 and T60 (1.182±0.136 versus 1.744±0.463); p=0.0173, in SIR group. In blood and tissue concentrations of pyruvate was found a significant increase in T0 (p=0.424), T30 (p=0.0271) and T60 (p=0.0175), and in brain tissue in T0 (p=0.0369) in the SIR group. In glucose blood concentrations there was a significant increase in T0 (0.493±0.393 versus 1.116±0.364); p=0.0174, T30 (0.617±0.356 versus 1.502±0.314); p=0.0010 and T60 (0.998±0.411 versus 1.718±0.477); p=0.0190, and in brain tissue in T0 (0.292±0.081 versus 0.952±0.7140); p=0.0484, T30 (0.264±0.080 versus 1.038±0.609); p=0.0116 and T60 (0.234±0.089 versus 0.985±0.533); p=0.0067, in the SIR group. On blood ketone bodies there was a significant increase in T0 (p=0.0006) and T60 (p=0.0455), and in brain tissue in T0 (p=0.0428) in SIR group. There was a significant increase in MPO enzyme levels at T0 (p<0.0001), T30 (p=0.0269) and T60 (p=0.0005). In the histopathological evaluation in the internal pyramidal and granular layers in group CRS observed a significant increase of pyknosis, red neurons, congestion and edema, at T0, T30 and T60. In the comparison between the (SIR) and (GIR) groups, there was a significant decrease in T0 (3.596±1.546 versus 1.960±0.450); p=0.0321, T30 (3.316±1.356 versus 1.971±0.568); p=0.0490 and T60 (2.409±0.801 versus 1.516±0.307); p=0.0290, and in brain tissue there was significant decrease in T0 (2,530±0,850 versus 1.540±0,302); p=0.0228. In brain tissue was found significant decrease in TBARS concentrations in T30 (0.110±0.006 versus 0.057±0.040); p=0.0102, and a significant increase of GSH in T0 (3.454±1.584 versus 10.054±2.880), p=0.0006, T30 (10.949±1.579 versus 81.767±9.060); p<0.0001 and T60 (101.83±2.631 versus 114.924±6.311); p=0.0011 in GIR group. Regarding the histological examination, a significant decrease of pyknosis was found at T30 (3.00 (2.75 to 4.25) versus 1.50 (0.75 to 2.00); p= 0.0086 and T60 (4.00 (3.75 to 5.55) versus 2.00 (1.75 to 4.00); p=0.0379 and red neurons at T30 (3,00 (2,00 to 4.25) versus 1.50 (0.75 to 2.00); p=0.0159 and T60 (4.00 (3.75 to 4.75) versus 2,00 (1.75 to 4.00); p= 0.0493. in the internal pyramidal layer. In the Internal granular layer in GIR group there was a significant reduction of pyknosis at T30 (2.00 (1.00 to 3.25) versus 1.00 (0.00 to 1.00); p=0.0208 and T60 1.50 (0.00 to 1.00) versus 0.00 (1.00 to 3.50); p=0.0412, red neurons in T30 (2.00 (1.00 to 3.25) versus 1.00 (0.00 to 1.00); p=0.0208 and T60 1.50 (0.00 to 1.00) versus 0.00 (1.00 to 3.50); p=0.0412 and on the intracerebral edema level at T30 (2.00 (1.00 to 2.00) versus 1.00 (0.75 to 1.00); p=0.0225. Therefore, the preconditioning with L-GLN-ALN is able to induce brain glicolise and promote a protective effect on ischemic brain injury and reperfusion in gerbils, since it increased the glutathione synthesis both on ischemia and reperfusion, as well as decreasing lipid peroxidation during the reperfusion phase and decreased the intercerebral edema level, and the number of pyknosys and red neurons in brain tissue.